PELATIHAN SCHEMA ACTIVATION STRATEGY DAPAT MENINGKATKAN PEMAHAMAN LITERASI SISWA - Tewarat, Sipri; Afriana, Afriana; Ambalegin, Ambalegin (ASOSIASI IDEBAHASA KEPRI, 2025)
This training was conducted at SMKS Gurindam Boarding School with the aim of enhancing students' reading comprehension skills through the implementation of the Schema Activation Strategy, supported by the integration of Morphological Awareness and Vocabulary Knowledge. The program was designed in response to the students' observed difficulties in understanding English texts, especially in identifying implicit information. The training included interactive sessions such as lectures, discussions, practical simulations, and assessments. Initially, students were introduced to the basic concepts of schema theory, word structure, and morphemes, followed by exercises connecting their prior knowledge to new information in reading texts. The integration of morphological understanding and vocabulary awareness allowed students to decode words and comprehend contextual meaning more effectively. The students demonstrated high enthusiasm and active participation throughout the sessions, indicating the relevance and effectiveness of the applied methods. Teachers also played a vital role in facilitating student engagement and ensuring the sustainability of the strategies introduced. Overall, based on the training activity and student’s score the program succeeded in fostering critical and analytical reading skills, equipping students with the tools necessary for long-term academic literacy development. This initiative highlights the importance of using targeted instructional strategies to address learning challenges and improve English literacy among vocational high school students.